Edhapic properties of a pampean caldenal soil in patches with different vegetation (Semiárida, 2018)
The Caldenal soils receive residues that vary in quantity and quality, according to the dominant vegetation. The aim of this work was to analyze the influence of the vegetation on the edaphic properties of the soil. An Entic Haplustoll was sampled by patches with the predominance of forage species (F), non forage under Calden (NF) and shrub (A). Fractions of organic carbon, total nitrogen, available phosphorus, exchangeable cations and hydrophobicity and infiltration parameters were determined. The NF soil presented high contents of total organic carbon and its fractions and also a high level of total nitrogen and phosphorous availability. In the F soil was found that the apparent density was higher and the exchangeable calcium content was lower. The surface of the soil in the F patch was classified as slightly water repellent, while the other soils’ surfaces were strongly repellent. The medium infiltration rate was lower for the NF patch soil and higher for the A patch soil, which had the highest final infiltration rate. Soil studies in the Caldenal are recommended to be realized with an experimental design that allows controlling the variability that the dominant vegetation causes on the surface, due to the influence that vegetation has on the edaphic properties of the soil.
Keywords: Caldén forest; Water infiltration; Sandy loam soil